Molecular mechanisms of memory reconsolidation - Tronson, Natalie C.; Taylor, Jane R. (Nature reviews. Neuroscience, 2007)
Key Points Reconsolidation has been conceptualized as a post-retrieval process that stabilizes memory made labile by retrieval. This theory remains controversial, and one major question is whether post-retrieval disruptions of memory are permanent, suggesting erasure and therefore a storage mechanism, or transient, suggesting that the memory trace remains intact. Molecular mechanisms of memory reconsolidation have been shown to have substantial but incomplete overlap with those of initial consolidation, supporting the assertion that reconsolidation may be a storage process. Studies utilizing inhibition and activation of intracellular signalling proteins have shown that transcription factors including CREB, C/EBPβ and ZIF268, as well as upstream protein kinases including PKA and ERK, are required for memory reconsolidation, Additional molecular cascades, including transcription factor ELK1, immediate early genes c- Fos and Sgk3 , and the protein kinase ERK are activated after memory reactivation, indicating a role for these pathways in reconsolidation. Disruption of memory reconsolidation may be useful for intervention in psychiatric disorders involving abnormally strong or intrusive memories, such as post-traumatic stress disorder. Abnormal reconsolidation processes might contribute to the development of psychiatric disorders such as drug addiction, where long-term adaptation of cell signalling pathways can contribute to ongoing enhancements of reconsolidation, thereby strengthening the maladaptive memory and leading to long-lasting, relapsing behavioural changes. In order to move forward and answer some of the ongoing controversies, research in reconsolidation needs to diverge from purely behavioural models to demonstrate electrophysiological and structural correlates of post-retrieval manipulations of memory. Memory reconsolidation theory is the subject of intensive recent research and debate. Tronson and Taylor outline the molecular events implicated in this process and discuss how elucidating its mechanisms could improve our understanding of normal and abnormal memory function. Memory reconsolidation has been argued to be a distinct process that serves to maintain, strengthen or modify memories. Specifically, the retrieval of a previously consolidated memory has been hypothesized to induce an additional activity-dependent labile period during which the memory can be modified. Understanding the molecular mechanisms of reconsolidation could provide crucial insights into the dynamic aspects of normal mnemonic function and psychiatric disorders that are characterized by exceptionally strong and salient emotional memories.